Merge, Operation and Space - Sanjaya Kumar Lenka (LingPoet: Journal of Linguistics and Literary Research, 2023)
This paper studies merge as a syntactic process of combining syntactic objects and argues that this combining process is always associated with a syntactic operation. This syntactic operation always follows an action operated by the syntactic objects on the basis of their grammatical properties. This action creates semantic space in which the derivation of a sentence takes place. This space has existence and it can be drawn from the structure of the sentence. There are different arguments and explanations about number of working space in which derivation of sentences takes place. But this paper argues that the derivation of a sentence takes place in the semantic space of this sentence itself and following this fact this paper argues that each sentence has specific semantic space. It means there is more than one semantic space seen in the derivation of different sentences. This paper follows the theoretical assumption of minimalist program given by Hornstein; 2017, Chomsky; 1995. This paper applies this theory in analysis of syntactic structure of an Indian language like Odia.